Stakeholder perspectives on mosque management and accountability: A stakeholder theory approach - Tufani, Jihan Alwiyah (International Journal Labs, 2024)
This study focuses on stakeholder assessments of mosque management. The researchers identified and investigated stakeholders' perceptions of mosque management using a descriptive qualitative case study of a historical mosque in the Sleman Regency. The concepts of stakeholder theory and accountability were used as part of the analytical framework. The results show that stakeholders view the religious programs and activities of the mosque positively, feeling that they benefit both the mosque and the surrounding community. Stakeholders also feel that the programs reflect the mosque’s commitment to building trust and stakeholder confidence. In terms of accountability, the mosque emphasizes moral, ethical, and spiritual accountability towards God and relationships with God and humans. Financial reporting is transparent, with reports posted publicly each month. Stakeholders believe that the chief administrator carries out his/her responsibilities honestly, openly, and responsibly. Overall, the research demonstrates the importance of considering stakeholder interests and aspirations to improve mosque management performance related to quality of services, transparency, accountability, and contributing to community development.